A Comparative Study of Speaking Ability between Students who Joined English Conversation Club and Those Who Did Not; A Case of English Department at Halu Oleo University - Bage, Sitti Rahmawati; Aderlaepe, Aderlaepe; Agustina, Sitti (Universitas Halu Oleo, 2021)
This study is conducted to examine whether there is a significant difference in speaking ability between students who join an English conversation club and those who do not. The design of the study was causal-comparative design. The population of the study was all 5th semester students of English Department at Halu Oleo University which consist of 77 students. The samples of the research were only 38 students. The researcher chose 19 students who joined English club by using purposive sampling and the researcher chose 19 students who did not by using random sampling. The data were analyzed by using SPSS in form of Independent Sample T-Test. The result of students’ speaking score shows that there is a significant difference between students who joined English conversation club and those who did not. It can be seen from the mean score of students who joined English conversation club was 75.00 while the mean score of students who did not join English conversation club was 62.63. In order to prove the hypothesis, the researcher took the conclusion by comparing the values of Sig (2 tailed) with the significance α value. It showed that the value of Sig (2 tailed) was 0.000 while the significance α value was 0.05. So, it can be concluded that the value of Sig (2 tailed) was lower than the significance o f α value (0.000 < 0.05). In other words, H0 was rejected and H1 totally accepted. It means that there is a significant difference of speaking ability between students who joined English conversation club and those who did not at English Department of 2017 at Halu Oleo University.